Determinants of Corporate Value in Indonesia Mining Sectors with Sustainability Performance as Mediating Variable - Yoyok Priyo Hutom; Tri Widyastuti; Darmansyah Darmansyah; Syahril Djaddang (Institut Bisnis dan Informatika Kesatuan, 2026)
Mining sector sustainability issues increasingly affect corporate financial performance. The novelty of this study lies in the integrative model demonstrating that under the SEOJK 16/2021 regime, sustainability performance functions as an economic translation mechanism that converts sustainability signals into market value. This study examined the relationship between asset value added, corporate social responsibility, and green accounting on sustainability performance and corporate value in the Indonesian mining sector for the period 2019–2023. This study used a quantitative method and applied PLS-SEM analysis based on secondary data obtained from annual reports and sustainability reports. Key findings indicated that all three variables have a significant positive effect on sustainability performance, with green accounting as the strongest contributor. However, only asset value added and sustainability performance have a direct effect on corporate value, while corporate social responsibility and green accounting do not. Through mediation analysis, sustainability performance was found to be a full mediator for corporate social responsibility and green accounting, and a partial mediator for asset value added regarding corporate value. Companies need to strengthen their environmental measurement systems and manage corporate social responsibility strategically to have a tangible impact on corporate value.